The Influence of Digital Literacy, Motivation, and Self-Efficacy on the Work Readiness of Students - Tiyanti, Nur Allizah Rio; Marsofiyati, Marsofiyati; Wolor, Christian Wiradendi (RADIANT: Journal of Applied, Social, and Education Studies, 2025)
Work readiness is the most important skill that students need to have to face the world of work. Work readiness consists of understanding, motivation, and individual ability to be able to perform work-related tasks efficiently, and must have physical, mental and emotional maturity. The preliminary research results show that many students are still hesitant to enter the workforce for several reasons. This is because they have concerns about how the work environment differs from school life.  The purpose of this study is to analyze the influence of digital literacy, motivation, and self-efficacy on the work readiness of grade XI students of SMK Negeri 12 Jakarta. Data in this study were collected through questionnaires, short interviews and surveys. The study involved grade X1 students from SMK Negeri 12 Jakarta. This study uses multiple linear regression to analyze the data. The hypotheses in this study will be tested using SPSS version 31.0.0.0. The findings of this study indicate that digital literacy has a negative and significant effect on work readiness, while motivation and self-efficacy have a positive and significant effect on work readiness. In addition, the findings indicate of this study indicate that students should improve digital literacy skills in accordance with work competencies, motivation and self-efficacy to be able to support readiness in the workplace.